A GENERAL INTRODUCTION INTO THE CORPORATE GOVERNANCE - BOGDAN RĂVAŞ; CRISTIAN ILIONI (Annals of the University of Petrosani: Economics)
The Corporate Governance Code establishes a set of rules and demanding that influence the management of a company in terms of strategic planning and decision making to optimize the interests of shareholders, creditors, customers, employees and employers.